SARS-CoV-2 infection of endothelial cells, dependent on flow-induced ACE2 expression, drives hypercytokinemia in a vascularized microphysiological system - Hatch, Christopher J.; Piombo, Sebastian D.; Fang, Jennifer S.; Gach, Johannes S.; Ewald, Makena L.; Van Trigt, William K.; Coon, Brian G.; Tong, Jay M.; Forthal, Donald N.; Hughes, Christopher C. W. (Frontiers in Cardiovascular Medicine, 2024)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus that causes coronavirus disease 2019 (COVID-19) has, to date, resulted in nearly 7 million deaths globally. Severe COVID-19 is associated with a hyperaggressive inflammatory response characterized by hypercytokinemia (i.e., "cytokine storm") and endothelial damage. The development of a vaccine for SARS-CoV-2 has reduced hospitalization rates, but hypercytokinemia remains a major concern among those with breakthrough infections leading to severe COVID-19. This suggests that disease models that recapitulate the COVID-19 hypercytokinemia response are still necessary. Our lab has previously developed a vascularized micro-organ (VMO) microphysiological system that supports de novo formation of a perfused and physiological microvasculature. Here, we adapt the VMO to model endothelial dysfunction following SARS-CoV-2 infection. We find that expression of reninangiotensin signaling axis components, which mediate SARS-CoV-2 cell entry, is preserved in endothelial cells in the VMO compared to 2D monolayer. Additionally, we show that SARS-CoV-2 pseudotyped virus has increased infectivity in the VMO compared to monolayer and that exposure of the VMO to SARS-CoV-2 pseudotyped virus reduces ACE2 expression. Finally, exposure of infected vasculature to recombinant Angiotensin leads to increased expression of several proinflammatory markers, including IL-6. In summary, we demonstrate using a vascularized microphysiological system that SARS-CoV-2 can infect vascular endothelial cells under flow conditions and that this may contribute to the hypercytokinemia frequently seen in COVID-19 patients.